Answer:
g(x) = x + 3
Explanation:
A composite function is a function that is written inside another function which means substituting one function into another function.
Ex: (fоg)(x) is a composite function, where x of f(x) is substituted by g(x)
∵ h(x) = (fоg)(x)
∵
![h(x)=√(x+5)](https://img.qammunity.org/2021/formulas/mathematics/college/adg9bm4q8vbvswmi0nfu5ooww12mdblplu.png)
∵
![f(x)=√(x+2)](https://img.qammunity.org/2021/formulas/mathematics/college/ho0kuvwqxkogk2n95msfgtq5u524udtja3.png)
→ Substitute x of f(x) by g(x)
∴ (fоg)(x) =
![√(g(x)+2)](https://img.qammunity.org/2021/formulas/mathematics/college/zl6uqkzh2ls7tk3bnj3izokwtxo5pegy2o.png)
→ Equate (fоg)(x) by h(x)
∴
![√(g(x)+2)=√(x+5)](https://img.qammunity.org/2021/formulas/mathematics/college/g3n7i68i0097zbbff42x62x0fpx6gzk7os.png)
→ Cancel the roots from the two sides
∴ g(x) + 2 = x + 5
→ Subtract 2 from both sides
∴ g(x) + 2 - 2 = x + 5 - 2
∴ g(x) = x + 3